2017
DOI: 10.1523/jneurosci.3361-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Prelimbic Cortex Attenuates Context-Dependent Operant Responding

Abstract: Operant responding in rats provides an analog to voluntary behavior in humans and is used to study maladaptive behaviors, such as overeating, drug taking, or relapse. In renewal paradigms, extinguished behavior recovers when tested outside the context where extinction was learned. Inactivation of the prelimbic (PL) region of the medial prefrontal cortex by baclofen/muscimol (B/M) during testing attenuates renewal when tested in the original acquisition context after extinction in another context (ABA renewal).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…Fewer studies have examined the neural basis of renewal in appetitive Pavlovian learning paradigms (Chaudhri et al, 2013;Anderson and Petrovich, 2017;Anderson and Petrovich, 2018b;Villaruel et al, 2018), and only a handful of studies have directly compared neural processes underlying ABA, AAB, and ABC renewal. Trask et al (2017) showed that pharmacological inactivation of the prelimbic cortex attenuated ABA renewal of operant responding for sucrose pellets; however, the same manipulation had no effect on ABC renewal in the same rats. In another study, Campese and Delamater (2013) found that pharmacological inactivation or lesions of the dorsal hippocampus had no effect on ABA or ABC renewal of Pavlovian responding to a cue that predicted food pellets (Campese and Delamater, 2013).…”
Section: Theoretical Methodological and Clinical Considerationsmentioning
confidence: 94%
“…Fewer studies have examined the neural basis of renewal in appetitive Pavlovian learning paradigms (Chaudhri et al, 2013;Anderson and Petrovich, 2017;Anderson and Petrovich, 2018b;Villaruel et al, 2018), and only a handful of studies have directly compared neural processes underlying ABA, AAB, and ABC renewal. Trask et al (2017) showed that pharmacological inactivation of the prelimbic cortex attenuated ABA renewal of operant responding for sucrose pellets; however, the same manipulation had no effect on ABC renewal in the same rats. In another study, Campese and Delamater (2013) found that pharmacological inactivation or lesions of the dorsal hippocampus had no effect on ABA or ABC renewal of Pavlovian responding to a cue that predicted food pellets (Campese and Delamater, 2013).…”
Section: Theoretical Methodological and Clinical Considerationsmentioning
confidence: 94%
“…In ABC renewal, testing occurs in Context C after conditioning and extinction have been conducted in A and B, respectively; in AAB renewal, testing occurs in Context B after conditioning and extinction have both occurred in Context A. Recent work in my laboratory suggests that all three forms of renewal do indeed occur after extinction of instrumental responding reinforced with food pellet reinforcers (Bouton, Vurbic, Todd, & Winterbauer, 2011; Todd, 2013; Todd, Winterbauer, & Bouton, 2012; Trask, Shipman, Green, & Bouton, 2017). Nakajima (2014) has also reported all three forms in an active shuttle-avoidance paradigm.…”
Section: Contextual Control Of Instrumental Extinction and Other Typementioning
confidence: 99%
“…The occasion setting concept is illustrated in Links 2 and 5 of Figure 1. It is notable that research in the 1980s and 1990s suggested the role of occasion setting by context in the control of Pavlovian extinction, where the idea is that contexts enable or retrieve CS-US relations, e.g., Context➜(S-O) (see Trask et al, 2017). We know that contexts can operate in an occasion-setting way in instrumental learning under some conditions.…”
Section: Mechanisms Of Contextual Controlmentioning
confidence: 99%
“…Interestingly, PL inactivation had no effect on renewal triggered by exposure to a novel context, following conditioning and extinction in separate, distinct contexts (ABC renewal), suggesting more specifically that the PL cortex may control instrumental behaviour that is guided by the conditioning context (Trask et al, 2017a).…”
Section: Introductionmentioning
confidence: 96%
“…In one such model, instrumental conditioning and test are conducted in the same context, whereas extinction is conducted in a second, distinct context (ABA renewal). Studies with non-drug or drug reinforcers indicate that functional inactivation of the PL cortex attenuated ABA renewal of instrumental behaviour (Eddy et al, 2016;Fuchs et al, 2005;Palombo et al, 2017;Trask et al, 2017a;Willcocks and McNally, 2013), suggesting that this region is required for controlling instrumental behaviour that is guided by contextual stimuli.…”
Section: Introductionmentioning
confidence: 99%